Gianotti-Crosti syndrome: exanthema following a vaccination - Widjaya, Suni C.; Mariam, Lysa (International Journal of Research in Dermatology, 2022)
Gianotti-Crosti syndrome (GCS) is a benign skin disorder characterized by self-limiting acute exanthema. Commonly preceding with the infection of viruses or bacteria and vaccinations. Usually affects children aged 1-6 years and is associated with atopic disease. The exact of GCS incidence is unknown, although several countries in the world have been reported GCS cases. Vaccine-induced GCS cases are infrequently reported. The diagnosis can be made clinically based on clinical features and vaccination history. Treatment is generally symptomatic. Education about GCS is important to prevent over-treatment and avoidance of vaccination in the future. We reported a 9-month-old baby with symmetrical bilateral monomorphic multiple dome-shaped papules lesions on the extremities two days following vaccination.